Further molecular and clinical delineation of co-locating 17p13.3 microdeletions and microduplications that show distinctive phenotypes. Issue 5 (7th May 2010) - Bruno, Damien L; Anderlid, Britt-Marie; Lindstrand, Anna; van Ravenswaaij-Arts, Conny; Ganesamoorthy, Devika; Lundin, Johanna; Martin, Christa Lese; Douglas, Jessica; Nowak, Catherine; Adam, Margaret P; Kooy, R Frank; Van der Aa, Nathalie; et al.
Abstract : Background: Chromosome 17p13.3 contains extensive repetitive sequences and is a recognised region of genomic instability. Haploinsufficiency of PAFAH1B1 (encoding LIS1) causes either isolated lissencephaly sequence or Miller–Dieker syndrome, depending on the size of the deletion. More recently, both microdeletions and microduplications mapping to the Miller–Dieker syndrome telomeric critical region have been identified and associated with distinct but overlapping phenotypes. Methods: Genome-wide microarray screening was performed on 7678 patients referred with unexplained learning difficulties and/or autism, with or without other congenital abnormalities. Eight and five unrelated individuals, respectively, were identified with microdeletions and microduplications in 17p13.3. Results: Comparisons with six previously reported microdeletion cases identified a 258 kb critical region, encompassing six genes including CRK (encoding Crk) and YWHAE (encoding 14-3-3ε). Clinical features included growth retardation, facial dysmorphism and developmental delay. Notably, one individual with only subtle facial features and an interstitial deletion involving CRK but not YWHAE suggested that a genomic region spanning 109 kb, encompassing two genes ( TUSC5 and YWHAE ), is responsible for the main facial dysmorphism phenotype. Only the microduplication phenotype included autism. The microduplication minimal region of overlap for the new and previously reported cases spans 72 kb encompassing a single gene, YWHAE . These genomic rearrangements were not associated with low-copy repeats and are probably due to diverse molecular mechanisms. Conclusions: The authors further characterise the 17p13.3 microdeletion and microduplication phenotypic spectrum and describe a smaller critical genomic region allowing identification of candidate genes for the distinctive facial dysmorphism (microdeletions) and autism (microduplications) manifestations.